Synthesis and Characterization of Low Loading MoO3/Ts-1 Catalyst - Suci Indrayani; Didik Prasetyoko (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
Abstract⎯Molybdenum oxide (MoO3) have been introduced to titanium silicalite (TS-1) by impregnation methode and have been characterized with X-ray diffraction (XRD), infrared spectroscopy, nitrogen and pyridine adsorption. The results show that TS-1 and XMoO3/TS-1 have orthorhombic structure and MFI framework structure type. 0,5% MoO3/TS-1, dan 1% MoO3/TS-1 catalyst have not been yet Brønsted acid site, while Brønsted acidity increased from 2% MoO3/TS-1 to 4% MoO3/TS-1 respectively.